Role of oxidative stress in the pathogenesis of vitiligo with special emphasis on the antioxidant action of narrowband ultraviolet B phototherapy. (June 2014) - Karsli, Neslihan; Akcali, Cenk; Ozgoztasi, Orhan; Kirtak, Necmettin; Inaloz, Serhat
Objectives: To evaluate the role of oxidative stress in the pathogenesis of vitiligo and the effect of narrowband (NB) ultraviolet (UV) B phototherapy on oxidative stress markers. Methods: Patients with vitiligo and healthy control subjects were included in the study. Patients in the vitiligo group were treated with an NB-UVB regimen (3 × weekly for 6 months). Erythrocyte superoxide dismutase activity (SOD), erythrocyte malonyldialdehyde (MDA) and erythrocyte glutathione peroxidase activity (GSH-Px) levels were assessed in all participants at baseline, and after NB-UVB phototherapy in patients with vitiligo. Results: A total of 24 patients with vitiligo and 27 control subjects were included in the study. Before treatment, erythrocyte MDA levels were significantly higher, and SOD and GSH-Px levels were significantly lower, in patients with vitiligo compared with controls. NB-UVB phototherapy was associated with a significant reduction in MDA levels and a significant increase in GSH-Px levels, compared with baseline, in patients with vitiligo. Conclusion: NB-UVB phototherapy may relieve oxidative stress in patients with vitiligo by reversing the oxidant–antioxidant imbalance that is considered to play a role in the pathogenesis of this disease.